Critical Discourse Analysis and the Editorial 2.0: News Reception and User-generated Comments in Discourses about (Im)migration (Altre Modernità, 2018)
In most traditional accounts of Critical Discourse Analysis (CDA) text and discourse are viewed as being the product of a one-directional flow of information from a handful of dominant (and powerful) text producers to an seemingly subordinate mass of readers who passively consume texts. To this end, CDA proclaims an interest in both production and reception factors as they are reflected in social practices (Fetzer & Johansson, 2008). Yet, in the CDA literature actual empirical data focusing on reception factors have often been lacking and/or have been limited to the researcher’s personal reading of a text. With the advent and spread of converged media platforms (Herring, 2013) and the new discourse practices this entails such factors need to be reconsidered and the more prominent role played by users in both reception and (co-)construction of texts embraced (Boyd, 2014). This work focuses on the importance of user-generated content in user comments written in response to online newspaper editorials and proposes that such commenting practices not only change media discourse and social practice but also, ultimately, may upend the traditional flow of media discourse, transforming it from a primarily top-down, one-to-many model to a more interactive and participatory model that fosters many-to-many participation schemes (KhosraviNik & Zia, 2014). In traditional print newspapers text consumers had few opportunities to respond directly to a topic they felt strongly about if not in the form of a “letter to the editor” which was not guaranteed publication. Furthermore, editorials, as the official mouthpiece of a news organisation, were seen as playing a predominant role in evaluating issues, forming public opinion and eliciting reader support and agreement (Henry & Tator, 2002; Moon, 1994; Van Dijk, 1991). Today, most online newspapers allow users to comment on both news reports and opinion articles, including editorials, in which they can react to as well as interact with media texts. Such social interaction gives the (CDA) researcher access to valuable user-generated content which can help to gauge, in part, the degree to which such media texts as editorials still have in forming and swaying public opinion. By focusing on reader comments in a limited set of editorials (dealing with the European migrant crisis), this study attempts to determine readers’ varying opinions about the issue and how this reflects and/or diverges from the view(s) presented by the editorial. A quantitative and qualitative analysis of the empirical data (the editorials and reader comments) aim to demonstrate the various representations of society inherent in online newspaper discourse. In particular, the analysis focuses on the linguistic means adopted by text producers to align themselves with (proximization) or differentiate themselves from (distancing) from the views presented in the editorial. Thus, the work is interested in the ways in which powerful public discourses are received by the general public through the interactive feature of text commenting available on many media platforms. Text commenting, in turn, is seen as crucial to understanding how certain texts are received and transformed by different types of (social) media users in the online newspaper.
Keywords: editorial; new media; CDA; CDA 2.0; Corpus linguistics